Importance of cone beam computed tomography for diagnosis of calcifying cystic odontogenic tumor associated to odontoma. Report of a case - Marques, Yonara-Maria-Freire-Soares; Botelho, Tessa-de Lucena; Xavier, Flavia-Calo-de Aquino; Rangel, Andrea-Leao [UNESP]; Rege, Inara-Carneiro-Costa [UNESP]; Mantesso, Andrea (Medicina Oral S L, 2010)
The calcifying cystic odontogenic tumour (CCOT) is a rare benign cystic neoplasm not infrequently associated with odontoma. This report documents a case of CCOT associated with compound odontoma arising in the anterior maxilla in a 25-year-old woman. Conventional radiographs showed a large calcified mass with poorly visualized radiolucent margins. The extent and condition of the internal structure of the CCOT associated with odontoma was able to be determined based on radiographic findings from cone beam computed tomography. This advanced image technique proved to be extremely useful in the radiographic assessment of this particular neoplasm of the jawbones.
Keywords: Cone beam computed tomography; conventional radiographs; calcifying cystic odontogenic tumour; compound odontoma